Amplification of major histocompatibility complex class II gene diversity by intraexonic recombination. - She, J X (1991)
The roles of mutational and recombinational processes in the diversification of the exon encoding the antigen binding site in the murine major histocompatibility complex class II gene Ab were assessed by phylogenetic analysis of allelic nucleotide sequences. A total of 46 alleles of Ab exon 2 from 12 Mus species or subspecies and 2 Rattus species were sequenced after amplification by the polymerase chain reaction. Reliable allelic genealogies could not be determined by phylogenetic analyses, due to extensive homoplasy in the data set. This homoplasy results from the shuffling of polymorphisms between alleles by recombinational processes, indicating that polymorphisms in the antigen binding site encoded by Ab are generated by a combination of two processes. First, the accumulation of point mutations has produced highly divergent polymorphic sequence motifs in five regions of Ab exon 2, each encoding a portion of the binding site. Some of these motifs have persisted as polymorphisms in rodents since before the divergence of mouse and rat (greater than 10 million years ago). The second process mediating Ab diversification involves the shuffling of these polymorphic sequence motifs into numerous allelic combinations by repeated intraexonic recombination. Site-specific hyperrecombinational mechanisms are not involved in this process within the exon. We postulate that these mechanisms continuously generate new Ab alleles with highly divergent binding sites from which alleles with advantageous antigen-binding properties are selectively maintained by some form of balancing selection.